Analysis of the Copper (Cu), Chromium (Cr), and Manganese (Mn) Levels from the Steel Industry Liquid Waste by Atomic Absorption Spectrophotometry Method - Alfian, Zul; Aini, Syarifah; Agusnar, Harry (Journal of Chemical Natural Resources, 2022)
Liquid waste from the steel industry processing, washing machine, and kitchenware foundry that is disposed containing copper (Cu), chromium (Cr) and manganese (Mn) elements which is harmful to enviromental. The levels of elemental copper (Cu), chromium (Cr), and manganese (Mn) were analyzed using Atomic Absorption Spectrophotometry (AAS) method. The effluent samples were destructed with the addition of concentrated HNO3. Then determining of the concentration of the element copper (Cu), chromium (Cr) and manganese (Mn) using Atomic Absorption Spectrophotometer with a calibration curve. The obtained results for the levels of copper (Cu) on the inlet samples were 0.9714 mg/L - 0.9719 mg/L, the outlet samples were 3.9990 mg/L - 4.0002 mg/L. Hence, the levels of the element chromium (Cr) on inlet samples were 0.0295 mg/L - 0.0297 mg/L, the outlet samples were 0.0399 mg/L - 0.0400 mg/L and the levels of manganese (Mn) in the inlet samples were 0.1269 mg/L - 0.1271 mg/L in a outlet samples were 2.9699 mg/L - 2.9701 mg/L. Then the steel industry wastewater for elemental copper (Cu) and manganese (Mn) has exceeded the limits that have been instituted by the Minister of Environment Decree No. 51, 1995, about the Liquid Waste Quality Standard for Industrial Activity